Flotation separation of fluorite from calcite by using psyllium seed gum as depressant. (1st December 2020) - Zhou, Hepeng; Zhang, Yongbing; Tang, Xuekun; Cao, Yijun; Luo, Xianping
Graphical abstract: Highlights: Psyllium seed gum (PSG) used as depressant in flotation process for the first time. The PSG has excellently selective depression effect on calcite. Flotation separation of fluorite from calcite can be achieved with PSG. The chemisorption dominates the interaction of PSG with calcite. Abstract: Separating fluorite and calcite through flotation is difficult due to their similar Ca 2+ sites on the adsorption surface of collectors. Psyllium seed gum, a reagent naturally derived from psyllium seed, was used for the first time as an efficient depressant in the flotation separation of fluorite and calcite. Micro-flotation experiments showed that psyllium seed gum had a strong depressing effect on calcite at a wide pH range (8–12). Calcite recovery was significantly and sharply reduced from 97.38% to less than 10% in the presence of psyllium seed gum at pH 9.0. By contrast, fluorite recovery was slightly affected by psyllium seed gum and maintained above 90%. FTIR analysis, XPS analysis, and adsorption test were conducted to determine the selective depression mechanism of psyllium seed gum on these two minerals, and the results show the adsorption effect and capacity of psyllium seed gum were stronger and higher on the calcite surface than on the fluorite surface. Owing to the high electronegativity and powerful electron-gaining ability of CO3 2−, many electron clouds moved from the hydroxyl groups of psyllium seed gum to the Ca, C, and O elements on the calcite surface. A large amount of psyllium seed gum was chemisorbed on the calcite surface by reacting with Ca 2+ site and preventing NaOl adsorption. On the contrary, psyllium seed gum barely affected NaOl adsorption on the fluorite surface. In this case, the efficient flotation separation of fluorite from calcite is realized.